Sperm Viability and Acrosome Integrity by Conventional and Fluorescent Staining Techniques Recovered in Three Different Buffers from Sheep Epididymal Tail- A Preliminary Study - Rasool Bhat, Ghulam; Ahmad Lone, Farooz; Preet Singh, Pawan; Rana, Sanchi (The Indian Journal of Animal Reproduction, 2025)
The study was carried out to evaluate the accuracy of conventional and fluorescence based staining techniques for via bility and acrosome integrity of cauda epididymal spermatozoa in sheep. Spermatozoa were recovered from fresh epi didymis of testicles collected from local slaughter houses. Spermatozoa were recovered in seminal plasma (SP), Tyrode’s Albumin Lactate Pyruvate (TALP) and Tris Methyl Aminomethane (TRIS) buffer. The recovered spermatozoa were eval uated immediately and stored at 4 °C for subsequent evaluation up to 72 hours. Sperm viability and acrosome integrity were assessed at 0, 24, 48 and 72 hours of recovery, using Eosin-Nigrosin and Carboxyfluorescein Diacetate (CFDA) plus Propidium Iodate (PI) for viability while Giemsa and Fluorescein Isothiocyanate-Peanut Agglutinin (FITC-PNA) plus PI for acrosome integrity. Upon general linear model statistics, the interactions viz; time x technique and buffer x time x technique were significant when TALP recovered spermatozoa were evaluated for viability and acrosome integrity, and when TRIS recovered spermatozoa were evaluated for acrosome integrity. By comparing the results at different periods, it was observed that the percentage values of both viability and acrosome integrity in SP recovered spermatozoa were significantly higher (p<0.05) when evaluated through conventional techniques. Compared to spermatozoa recovered in TALP and TRIS, those recovered in seminal plasma showed higher (p<0.05) sperm viability and acrosome integrity. Although the number of competent spermatozoa (possessing more percentage viability and acrosome integrity) were more in conventional staining methods, different classes of viable spermatozoa in all the replicates can be detected and better evaluated using fluorescent probes. In conclusion, fluorescent techniques proved more accurate and sensitive for evaluation of cauda epididymal spermatozoa in ram.